Infectious Endocarditis of a Heterotopic Caval Valved Stent - Mohammad Kassar, MD; Ana Ovsenik, MD; Nicolas Brugger, MD; Fabian Noti, MD; Joanna Bartkowiak, MD; Raouf Madhkour, MD; Babken Asatryan, MD, PhD; Thomas Baumgartner, MD; Christoph Gräni, MD, PhD; Fabien Praz, MD (JACC: Case Reports, 2023)
Right-sided infective endocarditis (IE) accounts for 5% to 10% of all IE cases. Compared with left-sided IE, it is more often associated with intravenous drug abuse and intracardiac devices, whereas the latter has become more prevalent in recent decades. The authors report the first case of IE in a heterotopic caval valved stent used for treating torrential tricuspid regurgitation. (Level of Difficulty: Advanced.)